2019
DOI: 10.4236/jhrss.2019.73027
|View full text |Cite
|
Sign up to set email alerts
|

Driving Innovation: Reviewing the Role of Rewards

Abstract: The role of rewards in promoting innovation has received considerable attention in both theory and practice. The fact that rewards have a positive impact on promoting innovation is well established. However, this relationship is complex since different types of rewards are suited for various kinds and stages of innovation. Further, an alternate view undermines the role of rewards in promoting innovation. Through an exhaustive literature review, this study illustrates the complex relationship between rewards an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The regression result for model 1 (see Table 5) has implicated that value-reward leadership practice significantly relates to productivity of the university's academic and non-academic staffs. Building on that premise it stands to affirm how enforcing integrative and coherent reward system, revolving around equity, justice, and fair play is critical to unleashing staff's creative and innovative thinking on one hand (Li, Chen, & Lai, 2017;Al Darmaki, Omar, & Wan Ismail, 2019) and the integrity and oneness of the group on the other hand (Fudge & Schlacter, 1999).…”
Section: Discussion Value Reward Leadership and Staff Productivitymentioning
confidence: 99%
“…The regression result for model 1 (see Table 5) has implicated that value-reward leadership practice significantly relates to productivity of the university's academic and non-academic staffs. Building on that premise it stands to affirm how enforcing integrative and coherent reward system, revolving around equity, justice, and fair play is critical to unleashing staff's creative and innovative thinking on one hand (Li, Chen, & Lai, 2017;Al Darmaki, Omar, & Wan Ismail, 2019) and the integrity and oneness of the group on the other hand (Fudge & Schlacter, 1999).…”
Section: Discussion Value Reward Leadership and Staff Productivitymentioning
confidence: 99%
“…With rewards given to teachers for their innovations, the anxiety associated with innovation among teachers may decrease. The previous result predicted that rewards are related to individual behavior 45 , 46 . Therefore, the reward factor may be able to encourage mathematics teachers to innovative behavior.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Rewards are important stimuli as innovation requires efforts and participation from employees that are not linked to their routine jobs. A higher degree of IP is expected to be achieved by organizations when their employees believe fair rewards system (Al Darmaki et al ., 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Further, RBV also help in understanding the HPWS-IP relationship by postulating that IP can be witnessed in organizations through the professional selection, training, appraising and rewarding of superior human capital (Bhatti et al, 2020;Al-Darmaki et al, 2019), to increase their motivation and commitment for creative thinking and innovation. Thus, based on the aforementioned discussion, it can be concluded that HPWS leads toward innovation performance and study proposes the following hypothesis.…”
Section: Hpws and Ipmentioning
confidence: 99%